08 SAFER 2: support and assessment for fall emergency referrals (part of the SAFER Research Programme). Issue 3 (1st March 2011) - Gaze, Sarah
Abstract : Introduction: Falls in older people have high human and organisational costs. Emergency 999 attendances to this group accounted for 8% of the total ambulance response in one year in London- of these calls, 40 % were not conveyed to hospital. This group is high risk for further falls and injuries. Recent UK policy changes have encouraged the development of alternative models of care by ambulance services, including enhanced paramedic training and community-based referral pathways. Aim: To assess the benefits and costs for patients and the NHS of new protocols allowing paramedics to assess and refer older people who have fallen to community based care. Main Objectives: Compare costs, processes and outcomes of care between experimental and control groups for: patient outcomes processes of care costs of care –NHS, social services, patients, carers. Gain an in-depth understanding of how new health technology is experienced by patients. Understand how the intervention is delivered in practice-identify factors which enable or hinder use. Methods: This Clustered Randomised Controlled Trial will recruit twenty-four participating stations (Clusters) from three sites- London, Nottingham and Wales, which will be randomised as Control (standard practice) or Intervention. Volunteer intervention paramedics (72) will receive additional training in the use of falls assessment and referral protocols and access to a new falls referral pathway. Eligible patients will be sent study questionnaires at 1 and 6 months and consent sought for health-related contacts to be tracked for 6 months following the initial 999 call. In-depth qualitative interviews (n=60 across 3 sites), focus groups with crews before and after implementation and with stakeholders will also occur. Measures of process, outcome and cost will be analysed according to 'intention to treat'. Qualitative data will be analysed thematically using a content analysis approach. Conclusion: This research will provide robust evidence for this new model of care, enabling ambulance services to make informed decisions about best use of their resources.